A LEGO brickumentary [videorecording (DVD)] - Davidson, Kief, 1970-; Junge, Daniel; Junge, Daniel; Bateman, Jason; Berard, Jamie (Anchor Bay Entertainment, 2015)
Since the birth of their trademark toy in 1958, The LEGO Group has produced over 400 billion bricks. But more and more, LEGO bricks aren't just for kids, and some take them very seriously. Adult Fans of LEGO around the globe are unashamedly declaring their love of the brick, brick artists are creating stunning and surprising creations, and LEGO master builders are building human scale and larger structures. This documentary playfully delves into the extraordinary impact of the LEGO brick.